2005
DOI: 10.1007/s11178-005-0343-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-Chemical Study on Positional Selectivity in the Trimethylsilylation and Sulfonation of Pyrrole and N-Alkylpyrroles

Abstract: Positional selectivity (α : β ratio) of electrophilic substitution in pyrrole, N-methylpyrrole, and N-tert-butylpyrrole was analyzed by ab initio , MP2/6-31G(d)//RHF/6-31G(d)] and DFT [B3LYP/6-31G(d)] calculations of some σ-complexes derived from the substrates. The results of calculations with the use as model electrophilic species of trimethylsilyl cation [MP2/6-31G(d)//RHF/6-31G(d) and B3LYP/6-31G(d)] and SO 3 molecule [B3LYP/6-31G(d)] instead of proton are fairly consistent with the experimental data, acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…The results from MP2/6-31G(d)//RHF/6-31G(d) and B3LYP/6-31G ( calculations for the σ-complexes formed by pyrrole, N-methylpyrrole, and N-(tert-butyl)pyrrole with the trimethylsilyl cation instead of a proton as model electrophile agree with experimental data on the formation of β-isomers during trimethylsilylation of pyrrole and its N-substituted derivatives with trimethylsilyl triflate even without taking into account the solvent effect [4]. However, the results from investigation of the sulfonation of the same pyrroles by the B3LYP/6-31G(p) method using the SO 3 molecule as electrophile [4] proved not so clear-cut, since they indicated a preference for the σ-complexes formed during attack at the α position but at the same time indicated greater thermodynamic preferability for the β-sulfonic acids and that it increased in the transition from pyrrole to N-methylpyrrole and then to N-(tert-butyl)pyrrole. In [4] to explain this contradiction it was suggested that the more stable σ-complexes formed during attack at the α position are transformed into the α-sulfonic acid more slowly than the isomeric σ-complexes formed during attack at the β-position are transformed into the β-sulfonic acid, and the amount of the minor β-intermediate is made up as a result of the reversibility of the first stage of sulfonation.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…The results from MP2/6-31G(d)//RHF/6-31G(d) and B3LYP/6-31G ( calculations for the σ-complexes formed by pyrrole, N-methylpyrrole, and N-(tert-butyl)pyrrole with the trimethylsilyl cation instead of a proton as model electrophile agree with experimental data on the formation of β-isomers during trimethylsilylation of pyrrole and its N-substituted derivatives with trimethylsilyl triflate even without taking into account the solvent effect [4]. However, the results from investigation of the sulfonation of the same pyrroles by the B3LYP/6-31G(p) method using the SO 3 molecule as electrophile [4] proved not so clear-cut, since they indicated a preference for the σ-complexes formed during attack at the α position but at the same time indicated greater thermodynamic preferability for the β-sulfonic acids and that it increased in the transition from pyrrole to N-methylpyrrole and then to N-(tert-butyl)pyrrole. In [4] to explain this contradiction it was suggested that the more stable σ-complexes formed during attack at the α position are transformed into the α-sulfonic acid more slowly than the isomeric σ-complexes formed during attack at the β-position are transformed into the β-sulfonic acid, and the amount of the minor β-intermediate is made up as a result of the reversibility of the first stage of sulfonation.…”
supporting
confidence: 70%
“…However, the results from investigation of the sulfonation of the same pyrroles by the B3LYP/6-31G(p) method using the SO 3 molecule as electrophile [4] proved not so clear-cut, since they indicated a preference for the σ-complexes formed during attack at the α position but at the same time indicated greater thermodynamic preferability for the β-sulfonic acids and that it increased in the transition from pyrrole to N-methylpyrrole and then to N-(tert-butyl)pyrrole. In [4] to explain this contradiction it was suggested that the more stable σ-complexes formed during attack at the α position are transformed into the α-sulfonic acid more slowly than the isomeric σ-complexes formed during attack at the β-position are transformed into the β-sulfonic acid, and the amount of the minor β-intermediate is made up as a result of the reversibility of the first stage of sulfonation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, investigation of the sulfonation of the same pyrroles by the B3LYP/6-31G(d) method using the SO 3 molecule as electrophile [6] did not give entirely unambiguous results. On the one hand they indicated a preference for the σ-complexes formed during attack at the α-position; on the other, they indicated greater thermodynamic preference for the β-sulfonic acids and a stronger preference in the transition from pyrrole to N-methylpyrrole and then to N-(tert-butyl)pyrrole.…”
mentioning
confidence: 95%
“…In fact, the results of quantum-chemical calculations by the MP2/6-31G(d)//RHF/6-31G(d) and B3LYP/6-31G(d) methods for the σ-complexes formed by pyrrole, N-methylpyrrole, and N-(tert-butyl)pyrrole with the trimethylsilyl cation and not the proton as model electrophile [6] agree with experimental data [3] on the formation of pyrrole and its N-substituted derivatives, β-substituted during trimethylsilylation with trimethylsilyltriflate, even if the solvent effect is not taken into account.…”
mentioning
confidence: 99%